Effects of Blended Learning in Teaching Mathematics in Higher Education - POKORNÝ, P.; HÍC, Pavel (Journal of Education, Technology and Computer Science, 2015)
Blended learning represents a combination of online learning and face-tofaceinstruction. While one group of researchers advocates the use of blendedlearning in teaching, others are more critical to the use of ICT in education. Thepaper deals with utilization of blended learning in teaching mathematics at Facultyof Education, Trnava University. From the results it follows that properintegration of ICT into teaching can make the teaching process more efficient.